Shared-knowledge, Transparency, and Accountability: In Enabling State-Society Relations Governance on COVID-19 Resilience Building Societies - Esien, Eddy Bruno (HAPSc Policy Briefs Series, 2020)
This policy brief examines shared-knowledge, transparency and accountability to improve enabling state-society relations on COVID-19 resilient building governance and takes into account the impact on third-country nationals (TCNs) in Austria, Finland, Czechia, and Lithuania. Existing research pointed to state-society relations as decentralised multi-stakeholder governance in public service reform for sustainable resilience building societies. However, the governance faced budgetary constraints and low public sector performance management. Although the relational governance shows certain public authorities have failed and/or ineffective to administer and achieve a range of public policy goals, there is still little policy study research in Nordic, Baltic, Central Eastern European- CEE and Central Western European countries explaining the improvement of state-society relations model on COVID-19 resilient building societies and its impacts to TCNs’ in the selected entities. Based on a qualitative cross-country oriented research approach with fewer country comparisons, primary data from the authors of this policy paper research, documents, published and unpublished scholarly texts are collected and analyzed with document and content analysis techniques. The findings indicates insufficient shared-knowledge for responsive decision to local concerns, lack of diverse interests groups’ consultations, and quality service delivery often not transparent that infringe the core values of trust, public accountability, mutual responsibilities, and citizens’ participation in effective public service relational governance implementation and impact TCNs and ethnic minorities peoples’ COVID-19 crisis-related resilient in the selected entities. This policy brief recommends shared-knowledge for open access to relevant information, mutual corporate responsibilities between government, public and private organization policy for public interest, diversify migrants communities involvement in policy consultation for open democracy, rebuilding of bureaucrats’ professional capacity to ensure commitment and increase public service staff, and legislation to set specific working ethics and values compatible with public interest that combine honesty, integrity, transparency, accountability, and fair equal treatment of citizens (especially from heterogeneous minorities subgroups) in the formulation, implementation, and delivery of public care to sustain COVID-19 resilient building societies. Not meeting these marginal policy adjustments and recommendations may intensify the reinforcement of public service distrust and corruption, deepen political and /or social inequalities, jeopardize open democracy, and impair sustainable COVID-19 resilient building societies.